Era of Maria Theresa (1717-1780) - نوفل وضاح (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Maria Theresa is named a lot of titles as Princess, Archduchess, Queen, and Empress; all of these titles had been held by Maria Theresa, however, her name was the most famous one. She made Her ruling era the prosperous era of the sacred Roman Empire of the German nation due to the noted reforms she made at all domains. Besides of that, Theresa was a stateswoman who knew how to utilize the political marriage and use it in the interest of her sons and daughters in order to strengthen the political alliances. This research is an attempt to shed the light on the most influential events and achievements at Theresa ruling era. Theresa ruled with her husband, Caesar France Stephan l, the sacred Roman Empire of the German nation in 1708-1765; however, his name had been marginalized a most of non-specialty studies because he did not descend from the imperial household of the Habsburg family.